(untitled) (ЕтноАнтропоЗум, 2011)
In 2010 in the production of the publishing house TABAHON from Skopje the book Pieces of Mosaic: an essay on the Making of Macedonia was released. It is a piece from an American anthropologist who lives and works in Denmark, Jonathan Matthew Schwartz.